Effect of pre‐operative oral paracetamol on gastric residual volume and pH in young children in the context of a 1‐hour clear fluid fast: a randomised controlled trial. (15th February 2022) - Saffer, E.; Nielsen, D. P. D.; Warwick, E.; Stilwell, A.; Webb, C.; Chow, G.; Place, M.‐K.
Summary: High gastric residual volume and low pH are associated with increased mortality following pulmonary aspiration in animal studies. The use of pre‐operative oral paracetamol has not been investigated in younger children and infants in the context of a prescriptive 1‐h clear fluid fast aimed at reducing the risk of pulmonary aspiration while improving patient experience. Children aged 1 month up to a weight of 25 kg and scheduled for elective surgery were randomly allocated to receive a prescribed 3.6 ml.kg ‐1 drink of water alone (water group) or 3 ml.kg ‐1 water and oral Infant Calpol® syrup (24 mg.ml ‐1 concentration, equivalent volume 0.6 ml.kg ‐1, paracetamol group) 1 h before the induction of anaesthesia. Following induction, a nasogastric tube was used to aspirate gastric contents and the volume and pH were recorded. Ninety‐seven children, median (IQR [range]) age 24 (12–45 [1–96]) months and weight 12.4 (9.7–16.0 [2.9–27.0]) kg, were analysed. Median time from drink to induction was 54 (45–60 [21–113]) min. There was no significant difference in gastric residual volume (p = 1) or pH (p = 0.99) between the water and the paracetamol groups. Sub‐group analysis revealed no significant difference in gastric residual volume or pH for 29 children who weighed < 10 kg compared with > 10 kg. Using a prescriptive fluid regime of 3 ml.kg ‐1 of water, the addition of oral paracetamol syrup did not significantly alter gastric residual volume or pH in the context of a 1‐h fast in infants and young children.